Protected geographical indications: Institutional roles in food systems governance and rural development. (March 2015) - Conneely, Ricky; Mahon, Marie
Highlights: Predominant food safety discourses undermine institutional support for PGI schemes. PGI as a place-based concept that must be devised in the first instance is overlooked. The potential of the scheme from a rural sustainability perspective is under-realised. The evident disconnect between food and rural policies weakens new rural economies. Abstract: This paper examines the importance of national-level institutional arrangements for promoting the EU's Protected Geographic Indication scheme (PGI). Taking the example of Ireland, for which PGI designations remain comparatively low, it explores whether the approach to providing institutional supports to the PGI scheme is influenced by top-down technocratic governance structures that pertain to food safety and quality certification that encompass the broader operating environment for food production in Ireland. Although the regulation of food safety and quality certification are distinct remits to the administration of the PGI scheme, in the Irish context the same institutional bodies are involved in governance of both. Using a discourse analysis interpretative framework, this paper draws on interviews with Irish producer group members and institutional representatives to examine how governance of the PGI scheme reflects management perspectives and practices more in keeping with a regulatory environment for food safety and quality than with development of place-based food product links. It suggests that incentives to avail of the PGI scheme as a means of realising value-added for producers are not well established because they require the development of more subjective, context-dependent processes and practices linked to geographical place and place identity. These are not easily accommodated under current institutional arrangements that also incorporate food safety and quality remits because these are in turn strongly established through nationally and internationally recognised systems of regulation and benchmarking. The findings point to the benefits to be gained from a more layered governance structure for PGI; devolving operation of the scheme to relevant regional and local development organisations that possess the expertise and relevant local knowledge to (a) incentivise the formation of producer groups, and (b) prioritise mentoring and support for PGI concept development as a clearer reflection of bottom-up rural sustainability policy.